Preservation of fish - Mumbai Archive Project Team (Jio Institute, 2024)
Once offloaded, the fish are preserved in ice and transported to wholesale markets. In Mumbai, there are several wholesale fish markets, including the Sassoon Dock Fish Market and Crawford Market, where the catch is further sorted, graded, and auctioned off to wholesalers, retailers, and fishmongers.